Social Media Content Personification and Brand-Consumer Engagement: Lessons from Corporate Organisations in Tanzania - Millambo, Revocatus Kaombwe; Urassa, Goodluck Charles; Karani, Michael (University of Dar es Salaam Library Journal, 2025)
Although the rise of social media as a vital channel of communication between companies and their customers has increased over time, there is limited evidence on how integrating human conversation content in online communication (brand personification) enhances brand-consumer engagement. To address this gap, we explored the human conversational content on social media pages of two corporate organisations in Tanzania and investigated their influence on brand-consumer engagement. Based on the analysis of 200 brand tweets and semi-structured interviews with 13 social media users, it was established that the most commonly used brand personification technique was message personalisation, encompassing personal greetings, addressing consumers personally, addressing employees personally, and using a personal signature. It was also evident that an informal speech (visual and tactile elements, informal language, audible elements, contractions/abbreviations and interjections/idiophones) and invitational rhetoric (stimulating dialogue, empathy, apologising, acknowledging, and well-wishing) were adopted to complement message personalisation. Furthermore, integrating brand personification techniques and ensuring instant response, active engagement, entertainment content, personalised communication, humour and appealing content enhanced brand-consumer engagement. Consistent with the Communication Accommodation and Integrated Marketing Communication theories, the study demonstrates that personification of marketing communication influences engagement between the brand and consumers. https://dx.doi.org/10.4314/udslj.v20i1.10